Comparative nanostructure analysis of gasoline turbocharged direct injection and diesel soot-in-oil with carbon black - Pfau, Sebastian A.; La Rocca, Antonino; Haffner-Staton, Ephraim; Rance, Graham A.; Fay, Mike W.; Brough, Robert J.; Malizia, Simone (Elsevier, 2018)
Two gasoline turbocharged direct injection (GTDI) and two diesel soot-in-oil samples were compared with one flame-generated soot sample. High resolution transmission electron microscopy imaging was employed for the initial qualitative assessment of the soot morphology. Carbon black and diesel soot both exhibit core-shell structures, comprising an amorphous core surrounded by graphene layers; only diesel soot has particles with multiple cores. In addition to such particles, GTDI soot also exhibits entirely amorphous structures, of which some contain crystalline particles only a few nanometers in diameter. Subsequent quantification of the nanostructure by fringe analysis indicates differences between the samples in terms of length, tortuosity, and separation of the graphitic fringes. The shortest fringes are exhibited by the GTDI samples, whilst the diesel soot and carbon black fringes are 9.7% and 15.1% longer, respectively. Fringe tortuosity is similar across the internal combustion engine samples, but lower for the carbon black sample. In contrast, fringe separation varies continuously among the samples. Raman spectroscopy further confirms the observed differences. The GTDI soot samples contain the highest fraction of amorphous carbon and defective graphitic structures, followed by diesel soot and carbon black respectively. The AD1:AG ratios correlate linearly with both the fringe length and fringe separation.